Depositional characteristics of a lacustrine mixed sediment system: A case study from the eastern Shijiutuo Uplift, offshore Bohai Bay Basin, eastern China. (15th April 2021) - Ye, Maosong; Xie, Xinong; Swennen, Rudy; Xu, Changgui; Du, Xiaofeng; Du, Xuebin
Graphical abstract: Highlights: Abundant mixed sediments were discovered in a siliciclastic-dominated continental setting. Prevailing nearshore bioclastics provided a foundation for the formation of "compositional mixing". Pre-existing siliciclastics and nearshore biota experienced secondary transportation, forming "compositional mixing". Lake-level rise resulted in the change of mixing types from "compositional mixing" to "strata mixing". Abstract: Mixed siliciclastic-carbonate sediments have been widely studied, especially those of marine origins. However, it is rarely investigated in continental settings. Boreholes from the Qinhuangdao-A (QHD-A) block in central Bohai Bay Basin sampled lacustrine mixed sediments during the Eocene period (32–38 Ma), providing an opportunity to facilitate this aspect of research. Here, an integrated study of seismic, core data, and microscopic analysis revealed the formation and evolution of the mixed sediment system. Core observations and microfossil identifications show that mixed sediments characterizing volcaniclastic sand and gravel mixed with bioclastic debris are composed of shallow-depth biota assemblages. The relatively warm climate, low tectonic activity and low siliciclastic influx may result in prevailing occurrences of nearshore biota. Preexisting siliciclastics featuring a well-rounding shape experienced secondary transportation to mix with the nearshore biota, forming the major mixing type (compositional mixing). Seismic data, well-logs, and lithofacies logs divided mixed sediments into three evolutional units (U1-U3). U1 and U2 were dominated by "compositional mixing". Within the U1, it occurred locally due to high sediment input during the low-level period. Peak took place in the U2 because lake-level rise led to increasing accommodation and decreasing siliciclastic influx. With further deepening of water depth in the U3, shallow-depended biota was not well developed and carbonates increased. Lake-level change results in a distinct depositional sequence of mixed sediments that bioclastic particles mixed with siliciclastics in shallow period and centimeter-scale carbonates interbedded with siliciclastic beds in the highstand. These findings bring new insights into mixed deposits, especially in continental settings.